ASSESSMENT LITERACY IN PPG BATCH 2020 - Bartholomeus Budiyono (Magister Scientiae, 2021)
One of the four competencies for professional teachers is the pedagogical competency that includes the ability to assess learning outcomes. This requirement should apply to teachers enrolled in teacher certification program (PPG). PPG Batch 20, however, did not provide teachers with any module for assessment literacy. This study administered a test to explore these teachers’ assessment literacy. The finding indicates that they belonged to the unacceptable-to-inadequate levels. An updated assessment literacy module is recommended to meet the purpose of assessment-literate teachers.